Rehabilitation of nature reserves in Jordan using GIS: an applied study on the Shaumari reserve in Azraq.... (Journal of the College of Basic Education, 2022)
In light of the growth of eco-tourism, which has become an important element in the tourism industry and developmenteconomic and social development at the international and local levels, as it represents an important and basic economic resourcecountries, especially those characterized by limited resources. Therefore, this study acquires special importance. Because Researching the rehabilitation of one of the successful means in the field of managing natural reserves using a system